Engineering Spider Genes for high-Tensile Silk and Patenting Challenges - Gupta, Vibhor; Rastogi, Sachin (Journal of Advanced Zoology, 2023)
This paper is a techno- legal review of existing scientific research, which explores the exciting field of genetic engineering and its potential in enhancing the tensile strength of spider silk through targeted modification of spider silk genes. Spider silk is renowned for its remarkable strength and flexibility, rendering it a highly coveted substance for many applications encompassing textiles, medical devices, and construction materials. However, its production on a large scale has been limited by the challenges of obtaining sufficient spider silk quantities. To overcome this limitation, researchers have turned to genetic engineering techniques to modify the genes responsible for spider silk production. This research delves into the development of novel techniques that enable precise and targeted modifications of these genes, aiming to enhance the tensile strength of spider silk even further. Additionally, this paper also addresses the legal challenges associated with patenting genetic modifications of spider silk genes. The unique nature of genetic engineering raises questions regarding patent eligibility, ownership, and potential infringement issues. This study discusses the current legal landscape surrounding patenting genetic modifications, including the criteria for patentability and the ethical considerations. By combining scientific advancements with legal insights, this research aims to contribute to the growing body of knowledge in the field of genetic engineering and provide a comprehensive understanding of the potential challenges and opportunities in enhancing spider silk’s tensile strength and protecting intellectual property rights.